2014
DOI: 10.1016/j.fob.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive hybridization‐mediated analysis of genes and in silico prediction of associated microRNAs under waterlogged conditions in sugarcane (Saccharum spp.)

Abstract: HighlightsWaterlogging adversely affects sugarcane productivity and quality.A subtractive cDNA library was prepared from sugarcane leaf tissue and sequenced to generate ESTs.EST sequences were used to identify transcripts induced by waterlogging.The sequenced clones were classified by predicted functions and stress-related genes formed the largest class.EST sequences were also used to identify putative novel microRNAs and their targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…Subtractive suppression hybridization is a powerful technique that enables researchers to compare two populations of mRNA and obtain clones of genes that are expressed in one population but not in the other (Almeida et al 2013;Ding et al 2014;Khan et al 2014). In the present study, drought stress responsive subtractive cDNA library was constructed from 22 days old pearl millet seedlings [P. glaucum cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtractive suppression hybridization is a powerful technique that enables researchers to compare two populations of mRNA and obtain clones of genes that are expressed in one population but not in the other (Almeida et al 2013;Ding et al 2014;Khan et al 2014). In the present study, drought stress responsive subtractive cDNA library was constructed from 22 days old pearl millet seedlings [P. glaucum cv.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various methods for differential transcriptome analysis, Suppression Subtractive Hybridization (SSH) proves to be an efficient approach to isolate and identify cDNAs of differentially expressed genes in the absence of sequence information (Mishra et al 2007;Almeida et al 2013;Ding et al 2014;Khan et al 2014). In this technique differentially expressed genes can be normalized and enriched over 1000-fold in a single round of hybridization (Diatchenko et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The gene SUFT, which is involved in the Fe/S cluster assembly pathway, has been reported that it is necessary for effective symbiosis to enhance iron availability [42]. Heat shock cognate 70 kDa protein is a chaperone which assist the folding of other proteins in vivo, and it was found to have increased expression in sugarcane plant subjected to WL treatment [43]. SAR1 in plants plays roles in GTPase activity, cargo secretion, membrane constriction, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The gene sufT, which is involved in the Fe/S cluster assembly pathway, has been shown necessary for effective symbiosis to enhance iron availability [29]. Heat shock cognate 70 kDa protein is a chaperone which assist the folding of other proteins in vivo, and it was found to have increased expression in sugarcane plant subjected to WL [30]. Sar1 in plants showing GTPase activity, cargo secretion, membrane constriction, etc.…”
Section: Comparison Of Protein Changes In Xm55 and Ym158 Under Wlmentioning
confidence: 99%